1981
DOI: 10.1111/j.2044-8309.1981.tb00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Races and faces — a comparison of the responses of Africans and Europeans to faces of the same and different races

Abstract: There is a popular belief that faces of members of races different from one's own 'look more alike' than those of one's own race. Empirical evidence shows that they differ in memorability. The present study was carried out to test the hypothesis that European and Afiican subjects differ from each other in the cues they use to discriminate among faces of their own and of the other race. Subjects reported the cues by carrying out sorting of triads of faces, and subsequently rating all faces on these cues. INDSCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 8 publications
1
46
0
2
Order By: Relevance
“…Our analysis of the association between skin color and attractiveness revealed an -other-race‖ effect, with variation in color cues strongly predicting attractiveness in own-ethnicity faces, whilst this relationship was absent for raters viewing other-ethnicity faces. This may be attributable to a lack of familiarity with other-ethnicity faces, and therefore a lack of familiarity with the meaning of cues in other-ethnicity faces (Shepherd & Deregowski, 1981). Moreover, the effect may be particularly strong in the present study as a consequence of the considerable difference in skin color between African and Caucasian groups which will mean that familiarity with these cues would be particularly limited (Valentine, 1991).…”
Section: Discussionmentioning
confidence: 61%
“…Our analysis of the association between skin color and attractiveness revealed an -other-race‖ effect, with variation in color cues strongly predicting attractiveness in own-ethnicity faces, whilst this relationship was absent for raters viewing other-ethnicity faces. This may be attributable to a lack of familiarity with other-ethnicity faces, and therefore a lack of familiarity with the meaning of cues in other-ethnicity faces (Shepherd & Deregowski, 1981). Moreover, the effect may be particularly strong in the present study as a consequence of the considerable difference in skin color between African and Caucasian groups which will mean that familiarity with these cues would be particularly limited (Valentine, 1991).…”
Section: Discussionmentioning
confidence: 61%
“…This own-group bias effect, sometimes labeled out-group homogeneity effect or cross-group deficit, is well documented. The own-bias effect has been found for such characteristics as age, attractiveness, race, and gender (e.g., Fulton & Bartlett, 1991;Lewin & Herlitz, 2002;Lindholm, 2005;Rodin, 1987;Shepherd & Deregowski, 1981;Wright & Sladden, 2003;Wright & Stroud, 2002). However, the explanations for the effects are still under debate.…”
Section: Own-group Biasmentioning
confidence: 99%
“…Finally, within-race rated similarity has shown, at best, only an inconsistent relationship to perception by own-race and other-race individuals, leading Goldstein and Chance (1979) to conclude that, overall, there is little "compelling evidence for the homogeneity hypothesis" (p. 111). We should note that although physiognomic homogeneity may not be responsible for the ORB memory effect, a number of studies have indicated that different physiognomic facial features may be more appropriate for discriminating between faces of certain races (Ellis, Deregowski, & Shepherd, 1975;Shepherd, 1981;Shepherd & Deregowski, 1981).…”
Section: Physiognomic Homogeneitymentioning
confidence: 99%